The Effect of Unparticle in the Processes \(e^+e^-→ γ γ\) and \(γ e^-→ U^μ e^-\) when the \(e^+,e^-\) Beams Are Polarized in Unparticle Physics - Thuy, Dao Thi Le; Thuc, Le Nhu (Communications in Physics, 2021)
We investigate the influence of unparticle physics on the positron-electron collider via the scalar unparticle and electron exchange. From computing the contribution of the unparticle exchange to the cross-section (CS) as well as evaluating the dependence of differential cross-section (DCS) on the scattering angle , we calculate the production of vector unparticle in the photon-electron collider in s- and t- channels such as missing energy distribution. Besides, we also found that the polarization of the beams also significantly contributes to the CS and DCS of the unparticle production.